I Had a Favorite Dress - Ashburn, Boni; Denos, Julia (New York : Abrams Books for Young Readers, 2011)
A young girl loves her favorite dress, but when it gets worn, goes out of fashion, or she grows too big to fit, her mother fixes up her old favorite into something new.
Accelerated Reader AR
Keywords: Clothing and dress -- Juvenile fiction -- Alteration; Clothing and dress -- Juvenile fiction; Sewing -- Juvenile fiction